طرق الاعتراض الشعبي على السلطة بين الدستور الجزائري والشريعة الإسلامية (مجلة الواحات للبحوث والدراسات, 2020)
The Research Addressed The Issue Of Popular Opposition To Power And Its Methods Established In The Algerian Constitution, And In Sharia, With A Statement Of The Compatibility And Contradictions Between Them, And Concluded That They Agree In Several Aspects, The Most Important One Is The  Opening The Field Of Objection To The Other Opinion, And Differing In What And How.Key Words - The Algerian Constitution, Sharia, Opposition, Parliament, Political Parties.